Characterization and fabrication of silver nanoparticles prepared by multiple methods and their antibacterial and antifungal effects (Texas Journal of Multidisciplinary Studies, 2024)
Various methods have been developed to produce silver nanoparticles with the aim of obtaining pollutantfree water. There is significant interest in developing production processes that are environmentally friendly and reducing the use of antibiotics. Chemical preparation methods utilizing various silver precipitants and physical methods have emerged to enhance the effectiveness of silver nanoparticles against small organisms, demonstrating potential biological applications in combating bacteria and fungi. Understanding the impact of silver placement on filters and its influence on bacteria, particularly Escherichia coli, a common bacterium, is crucial due to its association with other pollutants. This study explores the production of silver nanoparticles through two distinct biosynthesis methods. The manufactured silver is then utilized as an inhibitor for isolated bacteria and fungi, with subsequent separation of the silver nanoparticles prepared using both techniques. Various tests such as UV, FTIR, EDX, and AFM were conducted to analyze the properties of the nanoparticles. Additionally, changes in color from pale yellow to dark yellow were observed in the mixture of powder and colloidal liquid